(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the phagocytic, bacteriological, and lysozyme activity of the immune system of Karakul sheep bred in steppe, mountain, and foothill ecological zones, as well as the levels of immunoglobulins IgA, IgM, and IgG, by ecological zone and at different ages. Recommendations are given to increase the viability of Karakul sheep.